Development of the Composition and Technology for Production a Solid Dispersion System by Hot Melt Extrusion to Increase the Bioavailability of the Active Substance - K. A. Gusev; D. N. Maimistov; V. I. Pavlovsky; A. R. Aliev; A. V. Pavlovsky; O. V. Ivanova; D. O. Tsyrenov; E. V. Flisyuk (Разработка и регистрация лекарственных средств, 2022)
Introduction. The solubility of an active pharmaceutical ingredient plays a major role in drug absorption. Hot melt extrusion is a batch or continuous process that allows creating solid dispersion systems based on various carriers in order to increase solubility and bioavailability of active substances. Development of effective and safe analgesics is one of the most vital tasks of organic and medicinal chemistry. An innovative non-opioid analgesic with very low toxicity and low dosage, but practically insoluble in water, was used in this work. It was suggested to obtain a solid dispersion by hot melt extrusion in order to increase bioavailability.Aim. Development a hot melt extrusion technology for production of a solid dispersion system of PAV-0056 as an active substance and Plasdone™ S-630 as a polymeric carrier to increase the solubility.Materials and methods. PAV-0056 (methyl-2-(7-nitro-2-oxo-5-phenyl-3-propoxy-2,3-dihydro-1H-benzo[e][1,4]diazepin-1-yl)acetate) (JSC "Organica", Russia) Figure 1; Plasdone™ S-630 (Boai NKY Pharmaceuticals Ltd., China); PEG-1500 (Clariant, Switzerland); acetonitrile for chromatography (Thermo Fisher Scientific, Germany). Extrudates were obtained using a HAAKE™ MiniCTW co-rotating twin-screw laboratory extruder (Thermo Fisher Scientific, Germany). Extrudates were examined by optical microscopy and differential scanning calorimetry, and time of water solution stability was determined. The quantitative content of the active substance and related impurities in the 2.5 % solid dispersion of PAV-0056 was determined by HPLC-UV.Results and discussion. Hot melt extrusion process conditions were established for a mixture of 2.5 % PAV-0056 and Plasdone™ S-630. Stability of the extrudate solution in water was studied, the content of the active substance and impurities in the extrudates was determined. Based on the binary mixture, a composition containing 10 % of PEG-1500 was developed. The optimal conditions for the extrusion process were chosen for obtaining a solid dispersion system that meets the requirements of the regulatory documentation for the content of the active substance and impurities.Conclusion. The binary mixture proved to be unsuccessful for the creation of SDS by hot melt extrusion due to significant accumulation of impurities during the extrusion process. By adding PEG-1500 to the composition, it was possible to considerably lower the operating temperature of the process, reduce the impurity content in the extrudate, and maintain satisfactory stability of the PAV-0056 solution in water.